Is all support equal? The moderating effects of supervisor, coworker, and organizational support on the link between emotional labor and job performance - Hyun Jeong Kim; Won-Moo Hur; Tae Won Moon; Jea-Kyoon Jun (BRQ Business Research Quarterly, 2017)
This study was designed to examine the moderating roles of perceived supervisor, coworker, and organizational support in the relationship between emotional labor and job performance in the airline service context. A sample of flight attendants working for one major airline company in South Korea participated in this study. The flight attendants' official job performance data were provided by the airline company. For data analyses, a series of hierarchical moderated regression analyses were employed. The results showed differential moderation effects of the three sources of support at work. Specifically, the positive relationship between deep acting and job performance was strengthened by perceived supervisor and coworker support. The negative relationship between surface acting and job performance was exacerbated by perceived supervisor support, indicating the reverse buffering effect. Perceived organizational support showed only main effects on employee performance with no moderation effects."
Keywords: 650; Emotional labor; Organizational support; Supervisor support; Coworker support; Official job performance